KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU ( STUDI DI SMA NEGERI 2 PEMATANGSIANTAR) - Frank Endang Sari; Indra Prasetia; Elfrianto Elfrianto (STKIP ROKANIA, 2021)
This study aims to determine how the principal's transformational leadership in improving teacher performance and the principal's efforts in improving teacher performance at SMA Negeri 2 Pematangsiantar, through four components of the principal's ability, namely intellectual stimulation, individual consideration, inspirational motivation and idealistic influence. This study uses a descriptive approach and qualitative methods with observation, interviews and documentation techniques. The results of the study describe that the principal of SMA Negeri 2 Pematangsiantar in carrying out his leadership has implemented a transformational leadership style: (1) The principal of SMA Negeri 2 Pematangsiantar has given freedom to teachers to inspire and collaborate in conveying new ideas that are creative and innovative in transfer knowledge to students. (2) The principal of SMA Negeri 2 Pematangsiantar has been able to become a good listener for teachers who are facing problems and need attention and problem solving. (3) The principal of SMA Negeri 2 Pematangsiantar has set an example of good behavior and generates respect and is able to foster trust from teachers who later on the teacher will be imitated by the students. (4) Principal SMA Negeri 2 Pematangsiantar in acting, he always prioritizes the interests of the organization rather than personal interests.